SISTEM PAKAR DIAGNOSA PENYAKIT POLIP HIDUNG MENGGUNAKAN METODE LOGIKA FUZZY - Zulkarnain Zulkarnain; Lilis Indrayani (Politeknik Bisnis Indonesia, 2024)
The latest medical developments use computers to help diagnose diseases, one of which is an expert system is a computer program that incorporates human knowledge. Nasal polyps are disorders of the nasal mucosa in the form of soft masses that can cause obstruction of the respiratory tract. This study was designed to help in diagnosing nasal polyps by using 18 symptoms as a measure to determine whether or not nasal polyps are infected. To increase the validity of the research, the Fuzzy Logic method was employed in its completion. Three steps make up the Fuzzy Logic method: the fuzzification, inference, and deffuzification procedures. This system provides questions about the symptoms experienced by the patient. Following the patient's responses to the queries they have, the system will display the results of a diagnosis of shark polyps. To gauge the degree of accuracy, Mean Percentage Absolute Error (MAPE) is employed as a relative metric. The measurement findings revelaed a tiny inaccuracy 9%, indicating that the study’s accuracy level had achieved 90,9%. The findings also demonstrated a relationship between the weight of the symptoms and the probability values NOT, POSSIBLE and CONFIDENT.